Землеробство жителів поселень поблизу с. Волинцеве - Горбаненко, С.А. (Археологія, 2005)
Стаття вводить до наукового обігу нові матеріали із землеробства слов’ян Лівобережжя Дніпра з подальшою інтерпретацією даних. В статье собраны все имеющиеся на сегодняшний день сведения об уровне земледелия, засвидетельствованных для славянских поселений у с. Волынцево накануне образования Киевской Руси. Проанализированы орудия земледелия, а также расположение памятника на грунтах и палеоэтноботанический спектр. С некоторой долей вероятности можно сказать, что данные указывают на применение подсеки в начальный период освоения территории в качестве расширения полей. Вместе с тем, наличие широколезвийных наральников дает все основания констатировать активное введение перелоговой системы. The article combines all the data available concerning agricultural level of the Slavs having lived in the settlements near the village of Volyntseve on the ere of formation of the Kievan Rus\ The agricultural tools were analyzed, as well as the location of the monument with regards to soils and paleoethnobotanical aspects. With certain degree of probability these data indicate the slash method of widening the fields during the initial period of land development. At the same time the presence of wide-bladedtips enables ground to state that land rotation system was being introduced actively.